Focal status epilepticus as unique clinical feature of COVID-19: A case report. (May 2020) - Vollono, Catello; Rollo, Eleonora; Romozzi, Marina; Frisullo, Giovanni; Servidei, Serenella; Borghetti, Alberto; Calabresi, Paolo
Abstract: SARS-CoV-2, a novel zoonotic coronavirus, is currently spreading all over the world, causing a pandemic disease defined coronavirus disease 2019 (COVID-19). The spectrum of COVID-19 ranges from asymptomatic or mild infection to rapidly progressive, acute respiratory distress syndrome and death [1 ].To the best of our knowledge, status epilepticus has never been described as initial presentation of COVID-19. We report a patient affected by COVID-19 whose primary presentation was a focal status epilepticus.